Strengthening HRQOL Assessment in Singapore: Updated Norms for EQ-5D-5L and EORTC QLQ-C30 - Abdin, Edimansyah; Subramaniam, Mythily (Annals of the Academy of Medicine, Singapore, 2025)
Health-related quality of life (HRQOL) is increasingly used as an important indicator of health outcomes for measuring the impact of illness and treatment among individuals with mental or physical conditions. The EuroQol 5-dimension (EQ-5D) questionnaire is one of the most widely used generic measures for HRQOL and estimating the quality-adjusted life-years gained for economic evaluations of health treatments and programmes. The original version EuroQol 5-dimension 3-level (EQ-5D-3L) questionnaire contains 5 items covering 5 dimensions of HRQOL using 3 response levels, while the new version EuroQol 5-dimension 5-level (EQ-5D-5L) questionnaire has been expanded to 5 response levels to improve its sensitivity and reduce the ceiling effects.1 The scores from each dimension can be converted into an index score by applying country-specific value sets elicited from the general population. Given the lack of a gold standard in HRQOL measures, interpretation of the index scores requires population norm data as a reference point for identifying the burden of disease in patients with certain conditions or groups of patients. This can be done by comparing their profiles against an average person from similar characteristics, such as age and/or sex, in the general population.2